1998
DOI: 10.1128/mcb.18.6.3266
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Primary Initiation Sites for DNA Replication in the Hamster Dihydrofolate Reductase Gene Initiation Zone

Abstract: Mammalian replication origins appear paradoxical. While some studies conclude that initiation occurs bidirectionally from specific loci, others conclude that initiation occurs at many sites distributed throughout large DNA regions. To clarify this issue, the relative number of early replication bubbles was determined at 26 sites in a 110-kb locus containing the dihydrofolate reductase (DHFR)-encoding gene in CHO cells; 19 sites were located within an 11-kb sequence containing ori-␤. The ratio of ϳ0.8-kb nascen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
141
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(153 citation statements)
references
References 65 publications
12
141
0
Order By: Relevance
“…The reliability of this approach for ORI identification is supported by the fact that several mammalian ORIs that were initially identified by a variety of non-PCR approaches have been validated later by Q-PCR. Examples include the preferential initiation sites within the disperse initiation region downstream from the hamster DHFR gene identified by two-dimensional electrophoresis (Pelizon et al 1996;Kobayashi et al 1998), the human GM-CSF Ori1 and Ori2 identified by subtractive hybridization for origin capture (Todorovic et al 2005), and several human ORIs recently identified by high-throughput array hybridization (Lucas et al 2007). Conversely, ORIs initially identified by Q-PCR have been shown to bind ORC and MCM proteins as in the case of the human Lamin B2 (Abdurashidova et al 2003), c-Myc , and FMR1 (Gray et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of this approach for ORI identification is supported by the fact that several mammalian ORIs that were initially identified by a variety of non-PCR approaches have been validated later by Q-PCR. Examples include the preferential initiation sites within the disperse initiation region downstream from the hamster DHFR gene identified by two-dimensional electrophoresis (Pelizon et al 1996;Kobayashi et al 1998), the human GM-CSF Ori1 and Ori2 identified by subtractive hybridization for origin capture (Todorovic et al 2005), and several human ORIs recently identified by high-throughput array hybridization (Lucas et al 2007). Conversely, ORIs initially identified by Q-PCR have been shown to bind ORC and MCM proteins as in the case of the human Lamin B2 (Abdurashidova et al 2003), c-Myc , and FMR1 (Gray et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the site at which DNA synthesis initiates during amplification at DAFC-62D, nascent strand analysis was performed as described (16,17) on replicative intermediates isolated from stage 10B or 13 egg chambers. We observed a 1 kb region that was highly enriched in the 0.5-1 kb (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nascent Strand Length-To isolate nascent DNA of different lengths, CHO K1 cells were cultured and synchronized at their G 1 /S transition by a double aphidicolin block as described previously (8). The fraction of cells at their G 1 /S boundary was determined by fluorescence-activated cell sorting analysis to be Ͼ90%.…”
Section: Isolation Of Newly Synthesized Dna From Early Replication Bumentioning
confidence: 99%
“…For example, a 200-kb 1 region at the human ␤-globin gene (4, 5) and a 500-kb region at the mouse IgH gene (6) are both replicated from a single initiation locus. Moreover, what previously had been viewed as random initiation events distributed throughout "initiation zones" in Schizosaccharomyces pombe and hamster cells more likely reflects the presence of several strongly preferred initiation sites (7,8).Nevertheless, the precise size and composition of these initiation loci, as well as the parameters that define them remain the subject of intense investigation.The fact that specific sites for initiation of DNA replication can be developmentally acquired makes it clear that initiation sites in the metazoa are determined at least in part by epigenetic parameters. These parameters include nuclear structure, chromatin structure, and events that occur during G 1 phase of the cell division cycle (reviewed in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation